Health service needs and perspectives of remote forest communities in Papua New Guinea: study protocol for combined clinical and rapid anthropological assessments with parallel treatment of urgent cases. Issue 10 (31st October 2020) - Middleton, Jo; Abdad, Mohammad Yazid; Beauchamp, Emilie; Colthart, Gavin; Cooper, Maxwell J F; Dem, Francesca; Fairhead, James; Grundy, Caroline L; Head, Michael G; Inacio, Joao; Jimbudo, Mavis; Jones, Christopher Iain; et al.
Abstract : Introduction: Our project follows community requests for health service incorporation into conservation collaborations in the rainforests of Papua New Guinea (PNG). This protocol is for health needs assessments, our first step in coplanning medical provision in communities with no existing health data. Methods and analysis: The study includes clinical assessments and rapid anthropological assessment procedures (RAP) exploring the health needs and perspectives of partner communities in two areas, conducted over 6 weeks fieldwork. First, in Wanang village (population c.200), which is set in lowland rainforest. Second, in six communities (population c.3000) along an altitudinal transect up the highest mountain in PNG, Mount Wilhelm. Individual primary care assessments incorporate physical examinations and questioning (providing qualitative and quantitative data) while RAP includes focus groups, interviews and field observations (providing qualitative data). Given absence of in-community primary care, treatments are offered alongside research activity but will not form part of the study. Data are collected by a research fellow, primary care clinician and two PNG research technicians. After quantitative and qualitative analyses, we will report: ethnoclassifications of disease, causes, symptoms and perceived appropriate treatment; community rankings of disease importance and service needs; attitudes regarding health service provision; disease burdens and associations with altitudinal-related variables and cultural practices. To aid wider use study tools are in online supplemental file, and paper and ODK versions are available free from the corresponding author. Ethics and dissemination: Challenges include supporting informed consent in communities with low literacy and diverse cultures, moral duties to provide treatment alongside research in medically underserved areas while minimising risks of therapeutic misconception and inappropriate inducement, and PNG research capacity building. Brighton and Sussex Medical School (UK), PNG Institute of Medical Research and PNG Medical Research Advisory Committee have approved the study. Dissemination will be via journals, village meetings and plain language summaries.